2013
DOI: 10.1109/access.2013.2270173
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Angle-of-Arrival Estimation Via Real-Valued Sparse Representation With Circular Array Radar

Abstract: This paper suggests a real-valued sparse representation method using a unitary transformation that can convert complex-valued manifold matrices from uniform circular array into real ones. Because of this transformation, the computational complexity is modified. Simulation results confirmed the effectiveness of the proposed method with a circular array radar.INDEX TERMS Angle of arrival (AOA), array signal processing, uniform circular array (UCA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In other words, a considerable amount of computations can be saved if the complex‐valued DOA estimation problem in (11) can be replaced by real‐valued problem. In addition, Dai et al [24] and Kazemi et al [34] showed that the real‐valued methods can obtain better resolution ability and estimation accuracy than the complex‐valued methods. To avoid the limitation of unitary algorithms, we present a generalised RVSR for efficient single snapshot DOA estimation with arbitrary array configurations in this part.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…In other words, a considerable amount of computations can be saved if the complex‐valued DOA estimation problem in (11) can be replaced by real‐valued problem. In addition, Dai et al [24] and Kazemi et al [34] showed that the real‐valued methods can obtain better resolution ability and estimation accuracy than the complex‐valued methods. To avoid the limitation of unitary algorithms, we present a generalised RVSR for efficient single snapshot DOA estimation with arbitrary array configurations in this part.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…In recent years, much research has been done on the topic of localization by estimating the directions-of-arrival (DOA) (i.e., azimuth angles and elevation angles) and ranges of multiple targets in many applications, such as radar, sonar, and wireless communications [ 1 , 2 , 3 ]. Many methods based on one-dimensional (1D) uniform linear array (ULA) have been proposed for estimating azimuth angle [ 4 , 5 , 6 , 7 ], or joint range and azimuth angle estimation [ 8 , 9 ], such as the well-known multiple signal classification (MUSIC) algorithm [ 4 ] and estimation of signal parameters via rotational invariance techniques (ESPRIT) algorithm [ 5 ], and the generalized MUSIC and ESPRIT [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in this paper, the non-redundant TDOA measurements are used. Reference [5] studies the optimum sensor array of the source localization based on different measurements, such as Angle of Arrival (AOA) [9,10], Time of Arrival (TOA) [11,12], and Received Signal Strength (RSS) [13]. The optimality criterion used in [5] is maximizing the determinant of the FIM matrix.…”
Section: Introductionmentioning
confidence: 99%